A Research on Consumer Behaviour in the Industrial Valve market and Entry Strategy for Advanced Valve Technologies - Verma, Vishal (2005)
The importance of successful innovation for the long-term performance of companies can hardly be exaggerated. Although pioneers outsell late movers in many markets, in some cases innovative late entry has produced some remarkably successful brands that outsell pioneers.